2022
DOI: 10.46542/pe.2022.221.654663
|View full text |Cite
|
Sign up to set email alerts
|

The brain drain potential of skilled health workers from sub-Saharan Africa: A case study of pharmacy students in Nigeria

Abstract: Background: The increasing migration of health workers from low- and middle-income countries is an ongoing public health concern. This study evaluated the brain drain potential of pharmacy students in Nigeria.  Methods: This was a cross-sectional survey of final year pharmacy students from three Nigerian universities. Data collection was done via a 46-item self-administered questionnaire.     Results: There were 377 respondents. Reasons for potential emigration included better standard of living (n=334, 88.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In another operating business environment, the recent study of Zeng et al (2022) demonstrated the performance of Kenya's healthcare service delivery from government ineptitude nature through hybrid method. Another more recent study conducted by Amorha et al (2022) established potentials of brain-drain challenges of skilled healthcare employees. It is worthy to establish that none of these studies as recent as they were investigated the personnel brain-drain effect on quality healthcare delivery as this present study.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In another operating business environment, the recent study of Zeng et al (2022) demonstrated the performance of Kenya's healthcare service delivery from government ineptitude nature through hybrid method. Another more recent study conducted by Amorha et al (2022) established potentials of brain-drain challenges of skilled healthcare employees. It is worthy to establish that none of these studies as recent as they were investigated the personnel brain-drain effect on quality healthcare delivery as this present study.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While in Sierra Leone, a physician takes home as higher as $2000. Meanwhile, doctors in the United Kingdom, the USA and Saudi Arabia earn ten times higher than Nigerian doctors with a better work environment and retirement benefits (Amorha, Irobi, & Udoh, 2022). This naturally appeals to the sentiment of emigrating Nigerian doctors to these nations.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the idea of brain drain is widespread not only among medical students but also among students of nursing and other health professions shows that the negative effects of health policies on these groups should not be underestimated (15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…
Migration relates to the movement of a person from the usual place of residence to another place, within or across international borders, temporarily or permanently, and usually for different reasons (IOM, 2023). However, the common movement pattern is from a low-resource area to a high-resource area (e.g., rural to urban area) or a low-income to a high-income country (Amorha et al, 2022). This pattern of migration may result in a brain drain of the low-resource area and brain gain to the high-resource area (Anduaga-Beramendi et al, 2019).
…”
mentioning
confidence: 99%
“…indexes of the sending countries and its impact on widening the existing socioeconomic inequalities (Amorha et al, 2022).…”
mentioning
confidence: 99%